A kind of heat-resistant anti-creep adhesive and preparation method thereof
By combining modified alumina nanowires and phenolic epoxy resin, a temperature-resistant and creep-resistant adhesive was prepared, which solved the problem of degradation of existing adhesives at high temperatures and achieved good high temperature resistance, creep resistance and flame retardant properties.
Patent Information
- Application Number
- CN202411139739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-20
AI Technical Summary
Existing adhesives are prone to degradation and loss of strength in high temperature environments, limiting their application scope in engineering construction and other fields.
Modified alumina nanowires were obtained by reacting the alumina nanowires with 3-aminopropyltrimethoxysilane and polymerizing with phosphorous acid and ethylenediamine. Then, they were mixed with phenolic epoxy resin, functionalized alumina nanowires and N,N-dimethylformamide to prepare a temperature-resistant and creep-resistant adhesive.
The adhesive maintains good high temperature resistance, creep resistance and flame retardant under high temperature conditions, while improving its adhesion and bonding effect with the substrate.
Smart Images

Figure SMS_5 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, in particular to a temperature-resistant and creep-resistant adhesive and a preparation method thereof. Background Art
[0002] Adhesives are substances that can connect two or more materials together by generating physical adsorption, chemical bonding and mechanical bonding on the surface of solid materials. Compared with traditional connection technology, adhesive bonding does not require vias in bolt connection and riveting, which ensures the effective cross-sectional area of the material. While reducing the weight of the structure, it can also avoid structural deformation caused by high temperature in the welding process and make the most of the full strength of the bonded materials.
[0003] With the development of engineering construction, adhesive bonding technology is increasingly widely used in various industries and fields of the national economy, such as civil engineering, vehicle engineering, aerospace, and national defense. Many of these devices need to work for a long time under high-temperature loading conditions, and high-temperature environments easily cause adhesives to degrade and lose strength, limiting the application range of adhesives. Therefore, the present invention prepares an adhesive with excellent high-temperature resistance. Summary of the invention
[0004] The object of the present invention is to provide a temperature-resistant and anti-creep adhesive and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A heat-resistant and creep-resistant adhesive is obtained by uniformly mixing modified phenolic epoxy resin, functionalized alumina nanowires and N,N-dimethylformamide.
[0007] As an optimization, the modified novolac epoxy resin is obtained by reacting novolac epoxy resin, 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane.
[0008] As an optimization, the phenolic epoxy resin model is F51, which comes from Guangzhou Zeyiyuan Chemical Co., Ltd.
[0009] As an optimization, the functionalized alumina nanowires are obtained by reacting modified alumina nanowires with 4-(2-allyl)-catechol.
[0010] As an optimization, the modified alumina nanowires are obtained by reacting alumina nanowires with 3-aminopropyltrimethoxysilane and then polymerizing with phosphorous acid and ethylenediamine.
[0011] As an optimization, the alumina nanowires come from Qinghe County Ruijiang Metal Materials Co., Ltd.
[0012] A method for preparing a heat-resistant and creep-resistant adhesive comprises the following preparation steps:
[0013] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:(9-11), ultrasonically dispersed for 1-2 hours, 3-aminopropyltrimethoxysilane hydrolyzate was added in an amount of 1-2 times the mass of the alumina nanowires, stirred at 85-95°C and 200-300 rpm for 5-7 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 3-5 times, and dried at 75-85°C for 6-8 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:(1-2):(4-5), stirred at 60-70°C and 100-200 rpm for 20-30 minutes, ethylenediamine was added in an amount of 1.7-1.9 times the mass of the pre-modified alumina nanowires, stirred for 2-3 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 65-75°C for 8-10 hours to obtain modified alumina nanowires;
[0014] (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:(2-3):(0.01-0.02):(4-7), stirred in a nitrogen atmosphere at 80-90°C and 270-290 r / min for 9-11 h, naturally cooled to room temperature and filtered, washed with ethyl acetate for 3-5 times, and dried at 95-105°C for 8-10 h to obtain functionalized alumina nanowires;
[0015] (3) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:(0.6-0.7):(0.3-0.4):(6-8), add 0.9-1.1 mol / L sodium hydroxide solution to adjust the solution pH to 9-11, stir at 40-50°C and 400-500 rpm for 9-11 hours, cool naturally to room temperature, wash with deionized water for 3-5 times, and distill under reduced pressure at 115-125°C for 1-2 hours to obtain a modified phenolic epoxy resin;
[0016] (4) The modified phenolic epoxy resin and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.8~0.9) to obtain a modified phenolic epoxy resin solution; the functionalized alumina nanowires and an ethanol solution with a mass fraction of 80~90% are mixed in a mass ratio of 1:(3~4), stirred at 20~30°C and 270~290r / min for 30~40min, and the modified phenolic epoxy resin solution with a mass fraction of 61~62 times that of the functionalized alumina nanowires is added, and ultrasonic dispersion is performed for 25~35min to obtain a heat-resistant and creep-resistant adhesive.
[0017] As an optimization, the 3-aminopropyltrimethoxysilane hydrolyzate in step (1) is obtained by mixing 3-aminopropyltrimethoxysilane and 10% ethanol solution in a mass ratio of 1:11.
[0018] As an optimization, the reaction equation of the pre-modified alumina nanowires in step (1) is:
[0019] ;
[0020] As an optimization, the reaction equation for modifying the alumina nanowires in step (1) is:
[0021] ;
[0022] As an optimization, the reaction equation for functionalizing the aluminum oxide nanowires in step (2) is:
[0023] ;
[0024] As an optimization, the reaction equation of the modified phenolic epoxy resin in step (3) is:
[0025] ;
[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0027] When preparing the heat-resistant and creep-resistant adhesive, the invention comprises the following steps: reacting aluminum oxide nanowires with 3-aminopropyltrimethoxysilane, and then polymerizing with phosphorous acid and ethylenediamine to obtain modified aluminum oxide nanowires; reacting the modified aluminum oxide nanowires with 4-(2-allyl)-catechol to obtain functionalized aluminum oxide nanowires; reacting phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane to obtain modified phenolic epoxy resin; and uniformly mixing the modified phenolic epoxy resin, the functionalized aluminum oxide nanowires and N,N-dimethylformamide to obtain the heat-resistant and creep-resistant adhesive.
[0028] First, the aluminum oxide nanowires are reacted with 3-aminopropyltrimethoxysilane, and then polymerized with phosphorous acid and ethylenediamine to obtain modified aluminum oxide nanowires; the modified aluminum oxide nanowires are then reacted with 4-(2-allyl)-catechol to obtain functionalized aluminum oxide nanowires; 3-aminopropyltrimethoxysilane is grafted onto the aluminum oxide nanowires to improve the dispersibility of the aluminum oxide nanowires and enhance the high temperature resistance, creep resistance and flame retardancy of the heat-resistant and creep-resistant adhesive; diamine and diacid are polymerized to form long phosphoramide chains on the surface of the aluminum oxide nanowires, which are bonded to the surface of the aluminum oxide nanowires through strong hydrogen bonds. The effect is to improve the adhesion between the adhesive and the surface of the substrate and enhance the bonding effect of the heat-resistant and creep-resistant adhesive; at the same time, the phosphorus element in the phosphorous acid can form a non-flammable isolation layer at the combustion temperature, promote dehydration and carbonization, and capture oxygen free radicals, further improving the flame retardancy of the heat-resistant and creep-resistant adhesive; through the phosphorus-hydrogen addition grafting of 4-(2-allyl)-catechol, a catechol structure that can form a dynamic covalent five-membered ring with boric acid is introduced to form a cross-linked network while giving it reversibility, thereby improving the creep resistance and self-healing properties of the heat-resistant and creep-resistant adhesive.
[0029] Secondly, phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane are reacted to obtain modified phenolic epoxy resin; the modified phenolic epoxy resin, functionalized alumina nanowires and N,N-dimethylformamide are mixed to obtain a heat-resistant and creep-resistant adhesive; 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane are grafted by reacting epoxy groups with amino groups, and 4-aminophenylboronic acid pinacol ester is esterified with catechol to form a cross-linked network containing a dynamic covalent five-membered ring, thereby improving the creep resistance and self-healing properties of the heat-resistant and creep-resistant adhesive; the silanol groups produced by the hydrolysis of 3-aminopropyltrimethoxysilane are used to promote the formation of a siloxy cross-linked network, enhance the interfacial bonding strength between the adhesive and the substrate, and improve the high temperature resistance, creep resistance and bonding effect of the heat-resistant and creep-resistant adhesive. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0033] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:9, ultrasonically dispersed for 1 hour, 3-aminopropyltrimethoxysilane hydrolyzate of 1 times the mass of the alumina nanowires was added, stirred at 85°C and 200 rpm for 7 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 3 times, and dried at 75°C for 8 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:1:4, stirred at 60°C and 100 rpm for 30 minutes, ethylenediamine of 1.7 times the mass of the pre-modified alumina nanowires was added, stirred for 3 hours and filtered, washed with anhydrous ethanol for 3 times, and dried at 65°C for 10 hours to obtain modified alumina nanowires;
[0034] (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:2:0.01:4, stirred at 80°C and 270 r / min for 11 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with ethyl acetate three times, and dried at 95°C for 10 h to obtain functionalized alumina nanowires;
[0035] (3) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:0.6:0.3:6, add 0.9 mol / L sodium hydroxide solution to adjust the solution pH to 9, stir at 40°C and 400 rpm for 11 hours, cool naturally to room temperature, wash with deionized water for 3 times, and distill under reduced pressure at 115°C for 2 hours to obtain a modified phenolic epoxy resin;
[0036] (4) The modified phenolic epoxy resin and N,N-dimethylformamide were mixed in a mass ratio of 1:0.8 to obtain a modified phenolic epoxy resin solution; the functionalized alumina nanowires and 80% ethanol solution were mixed in a mass ratio of 1:3, stirred at 20°C and 270 r / min for 40 min, and the modified phenolic epoxy resin solution (61 times the mass of the functionalized alumina nanowires) was added, and ultrasonic dispersion was performed for 35 min to obtain a heat-resistant and creep-resistant adhesive.
[0037] Embodiment 2:
[0038] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0039] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:10, ultrasonically dispersed for 1.5 hours, 3-aminopropyltrimethoxysilane hydrolyzate in an amount of 1.5 times the mass of the alumina nanowires was added, stirred at 90°C and 250 rpm for 6 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 4 times, and dried at 80°C for 7 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:1.5:4.5, stirred at 65°C and 150 rpm for 25 minutes, ethylenediamine in an amount of 1.8 times the mass of the pre-modified alumina nanowires was added, stirred for 2.5 hours and filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 9 hours to obtain modified alumina nanowires;
[0040] (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:2.5:0.015:5.5, stirred at 85°C and 280 r / min for 10 h in a nitrogen atmosphere, naturally cooled to room temperature and then filtered, washed with ethyl acetate for 4 times, and dried at 100°C for 9 h to obtain functionalized alumina nanowires;
[0041] (3) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:0.65:0.35:7, add 1 mol / L sodium hydroxide solution to adjust the solution pH to 10, stir at 45°C and 450 rpm for 10 h, cool naturally to room temperature, wash with deionized water 4 times, and distill under reduced pressure at 120°C for 1.5 h to obtain a modified phenolic epoxy resin;
[0042] (4) The modified phenolic epoxy resin and N,N-dimethylformamide were mixed at a mass ratio of 1:0.85 to obtain a modified phenolic epoxy resin solution; the functionalized alumina nanowires and 85% ethanol solution were mixed at a mass ratio of 1:3.5, stirred at 25°C and 280 r / min for 35 min, and the modified phenolic epoxy resin solution (61.5 times the mass of the functionalized alumina nanowires) was added, and ultrasonic dispersion was performed for 30 min to obtain a heat-resistant and creep-resistant adhesive.
[0043] Embodiment 3:
[0044] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0045] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:11, ultrasonically dispersed for 2 hours, 3-aminopropyltrimethoxysilane hydrolyzate was added in an amount twice the mass of the alumina nanowires, stirred at 95°C and 300 rpm for 5 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 5 times, and dried at 85°C for 6 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:2:5, stirred at 70°C and 200 rpm for 20 minutes, ethylenediamine was added in an amount 1.9 times the mass of the pre-modified alumina nanowires, stirred for 2 hours and filtered, washed with anhydrous ethanol for 5 times, and dried at 75°C for 8 hours to obtain modified alumina nanowires;
[0046] (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:3:0.02:7, stirred at 90°C and 290 r / min for 9 h in a nitrogen atmosphere, naturally cooled to room temperature and then filtered, washed with ethyl acetate for 5 times, and dried at 105°C for 8 h to obtain functionalized alumina nanowires;
[0047] (3) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:0.7:0.4:8, add 1.1 mol / L sodium hydroxide solution to adjust the solution pH to 11, stir at 50°C and 500 rpm for 9 h, cool naturally to room temperature, wash with deionized water 5 times, and distill under reduced pressure at 125°C for 1 h to obtain a modified phenolic epoxy resin;
[0048] (4) The modified phenolic epoxy resin and N,N-dimethylformamide were mixed in a mass ratio of 1:0.9 to obtain a modified phenolic epoxy resin solution; the functionalized alumina nanowires and a 90% ethanol solution were mixed in a mass ratio of 1:4, stirred at 30°C and 290 r / min for 30 min, and the modified phenolic epoxy resin solution (62 times the mass of the functionalized alumina nanowires) was added, and ultrasonic dispersion was performed for 35 min to obtain a heat-resistant and creep-resistant adhesive.
[0049] Comparative Example 1
[0050] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0051] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:10, ultrasonically dispersed for 1.5 hours, 3-aminopropyltrimethoxysilane hydrolyzate in an amount of 1.5 times the mass of the alumina nanowires was added, stirred at 90°C and 250 rpm for 6 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 4 times, and dried at 80°C for 7 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:1.5:4.5, stirred at 65°C and 150 rpm for 25 minutes, ethylenediamine in an amount of 1.8 times the mass of the pre-modified alumina nanowires was added, stirred for 2.5 hours and filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 9 hours to obtain modified alumina nanowires;
[0052] (2) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:0.65:0.35:7, add 1 mol / L sodium hydroxide solution to adjust the solution pH to 10, stir at 45°C and 450 rpm for 10 h, cool naturally to room temperature, wash with deionized water 4 times, and distill under reduced pressure at 120°C for 1.5 h to obtain a modified phenolic epoxy resin;
[0053] (3) The modified phenolic epoxy resin and N,N-dimethylformamide were mixed at a mass ratio of 1:0.85 to obtain a modified phenolic epoxy resin solution; the modified alumina nanowires and 85% ethanol solution were mixed at a mass ratio of 1:3.5, stirred at 25°C and 280 r / min for 35 min, and the modified phenolic epoxy resin solution (61.5 times the mass of the modified alumina nanowires) was added, and ultrasonic dispersion was performed for 30 min to obtain a heat-resistant and creep-resistant adhesive.
[0054] Comparative Example 2
[0055] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0056] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:10, ultrasonically dispersed for 1.5 hours, allyltrimethoxysilane hydrolyzate with a mass of 1.5 times that of the alumina nanowires was added, stirred at 90°C and 250 rpm for 6 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 4 times, and dried at 80°C for 7 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:2.5:0.015:5.5, stirred at 85°C and 280 r / min for 10 hours in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with ethyl acetate for 4 times, and dried at 100°C for 9 hours to obtain modified alumina nanowires;
[0057] (2) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:0.65:0.35:7, add 1 mol / L sodium hydroxide solution to adjust the solution pH to 10, stir at 45°C and 450 rpm for 10 h, cool naturally to room temperature, wash with deionized water 4 times, and distill under reduced pressure at 120°C for 1.5 h to obtain a modified phenolic epoxy resin;
[0058] (3) The modified phenolic epoxy resin and N,N-dimethylformamide were mixed at a mass ratio of 1:0.85 to obtain a modified phenolic epoxy resin solution; the modified alumina nanowires and 85% ethanol solution were mixed at a mass ratio of 1:3.5, stirred at 25°C and 280 r / min for 35 min, and the modified phenolic epoxy resin solution (61.5 times the mass of the modified alumina nanowires) was added, and ultrasonic dispersion was performed for 30 min to obtain a heat-resistant and creep-resistant adhesive.
[0059] Comparative Example 3
[0060] A method for preparing a heat-resistant and anti-creep adhesive, the method comprising the following preparation steps:
[0061] (1) Alumina nanowires and n-butanol were mixed in a mass ratio of 1:10, ultrasonically dispersed for 1.5 hours, 3-aminopropyltrimethoxysilane hydrolyzate in an amount of 1.5 times the mass of the alumina nanowires was added, stirred at 90°C and 250 rpm for 6 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol for 4 times, and dried at 80°C for 7 hours to obtain pre-modified alumina nanowires; pre-modified alumina nanowires, phosphorous acid and anhydrous ethanol were mixed in a mass ratio of 1:1.5:4.5, stirred at 65°C and 150 rpm for 25 minutes, ethylenediamine in an amount of 1.8 times the mass of the pre-modified alumina nanowires was added, stirred for 2.5 hours and filtered, washed with anhydrous ethanol for 4 times, and dried at 70°C for 9 hours to obtain modified alumina nanowires;
[0062] (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:2.5:0.015:5.5, stirred at 85°C and 280 r / min for 10 h in a nitrogen atmosphere, naturally cooled to room temperature and then filtered, washed with ethyl acetate for 4 times, and dried at 100°C for 9 h to obtain functionalized alumina nanowires;
[0063] (3) Phenolic epoxy resin and N,N-dimethylformamide were mixed in a mass ratio of 1:0.85 to obtain a phenolic epoxy resin solution; functionalized alumina nanowires and 85% ethanol solution were mixed in a mass ratio of 1:3.5, stirred at 25°C and 280 r / min for 35 min, and a modified phenolic epoxy resin solution (61.5 times the mass of the functionalized alumina nanowires) was added, and ultrasonic dispersion was performed for 30 min to obtain a heat-resistant and creep-resistant adhesive.
[0064] Test Case
[0065] The heat-resistant and anti-creep adhesives obtained in the examples and the comparative examples were coated on polytetrafluoroethylene films to a thickness of 3 mm, and cured at 100° C. for 4 hours to obtain heat-resistant and anti-creep adhesive films.
[0066] 1. High temperature resistance
[0067] Test method: The heat-resistant and creep-resistant adhesive films obtained in each embodiment and the comparative example were taken with the same size, and the thermal weight loss rate was tested at 300°C and an O2 flow rate of 10 mL / min using German Netzsch TG209F3.
[0068] 2. Creep resistance
[0069] Test method: The heat-resistant and creep-resistant adhesive films obtained in each embodiment and the comparative example were cut into samples with a diameter of 25 mm, and the creep recovery rate was tested using an Anton Paar MCR302 rotational rheometer at 25°C, loading stress τ=30000 Pa, stress loading time 300s, and creep recovery time 600s.
[0070] 3. Self-healing
[0071] Test method: Take two 100mm×100mm samples of the heat-resistant and creep-resistant adhesive films obtained in each embodiment and the comparative example, test the tensile strength σ0 of one sample at a rate of 10mm / min, and cut the same scratches on the other sample with a cutter. After standing at 80℃ for 2h, test the tensile strength σ1 at a rate of 10mm / min, calculate the strength retention rate = σ1 / σ0*100%, and judge the self-healing performance.
[0072] 4. Flame retardancy
[0073] Test method: The heat-resistant and creep-resistant adhesive films obtained in each embodiment and the comparative example were cut into samples of 100 mm×6 mm in size, and the limiting oxygen index was tested according to GB / T2406.
[0074] 5. Bonding effect
[0075] Test method: The heat-resistant and creep-resistant adhesives obtained in each embodiment and the comparative example were coated on both sides of the rubber substrate at 25°C according to GB / T13936, and the steel substrates were glued on both sides. They were left standing at 80°C for 10 hours, and the shear strength was measured at a rate of 50 mm / min using a 5567 tensile testing machine.
[0076] Table 1 below shows the analysis results of high temperature resistance, creep resistance, self-healing property, flame retardancy and bonding effect of the heat-resistant and creep-resistant adhesives of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0077] Table 1
[0078]
[0079] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the heat-resistant and creep-resistant adhesive prepared by the present invention has good high temperature resistance, creep resistance, self-healing property, flame retardancy and bonding effect.
[0080] By comparison, the creep recovery rate and strength retention rate of Examples 1, 2, and 3 are higher than those of Comparative Example 1, indicating that by grafting 4-(2-allyl)-catechol via phosphine-hydrogen addition, a catechol structure capable of forming a dynamic covalent five-membered ring with boric acid is introduced to form a cross-linked network while imparting reversibility, thereby improving the creep resistance and self-healing properties of the heat-resistant and creep-resistant adhesive.
[0081] By comparison, the limiting oxygen index and shear strength of Examples 1, 2, and 3 are higher than those of Comparative Example 2, which indicates that by utilizing the polymerization of diamine and diacid, long chains of phosphoramide are formed on the surface of alumina nanowires, and the adhesion between the adhesive and the substrate surface is improved through strong hydrogen bonding, thereby enhancing the bonding effect of the heat-resistant and creep-resistant adhesive. At the same time, the phosphorus element in the phosphorous acid can form a non-flammable isolation layer at the combustion temperature, promote dehydration and carbonization, and capture oxygen free radicals, thereby further improving the flame retardancy of the heat-resistant and creep-resistant adhesive.
[0082] By comparison, Examples 1, 2, and 3 have lower thermal weight loss rates than Comparative Example 3 and higher creep recovery rates, strength retention rates, and shear strengths, indicating that 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane are grafted by reacting epoxy groups with amino groups, and 4-aminophenylboronic acid pinacol ester is esterified with catechol to form a cross-linked network containing a dynamic covalent five-membered ring, thereby improving the creep resistance and self-healing properties of the heat-resistant and creep-resistant adhesive. The silanol groups produced by the hydrolysis of 3-aminopropyltrimethoxysilane are used to promote the formation of a siloxy cross-linked network, enhance the interfacial bonding between the adhesive and the substrate, and improve the high temperature resistance, creep resistance, and bonding effect of the heat-resistant and creep-resistant adhesive.
[0083] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a heat-resistant and creep-resistant adhesive, characterized in that: The heat-resistant and creep-resistant adhesive is obtained by mixing modified phenolic epoxy resin, functionalized alumina nanowires and N,N-dimethylformamide; The modified phenolic epoxy resin is obtained by reacting phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester and 3-aminopropyltrimethoxysilane; The functionalized alumina nanowires are obtained by reacting modified alumina nanowires with 4-(2-allyl)-catechol; The modified alumina nanowires are obtained by reacting alumina nanowires with 3-aminopropyltrimethoxysilane and then polymerizing with phosphorous acid and ethylenediamine; The preparation method of the heat-resistant and creep-resistant adhesive comprises the following preparation steps: (1) 3-aminopropyltrimethoxysilane and 10% ethanol solution were mixed at a mass ratio of 1:11 to obtain 3-aminopropyltrimethoxysilane hydrolyzate; alumina nanowires and n-butanol were mixed at a mass ratio of 1:(9-11), ultrasonically dispersed for 1-2 h, 3-aminopropyltrimethoxysilane hydrolyzate with a mass of 1-2 times that of alumina nanowires was added, stirred at 85-95 °C and 200-300 rpm for 5-7 h, cooled naturally to room temperature, filtered, and washed with anhydrous ethanol for 3-5 min. The pre-modified alumina nanowires were mixed with phosphorous acid and anhydrous ethanol in a mass ratio of 1:(1-2):(4-5), stirred at 60-70°C and 100-200 rpm for 20-30 min, and 1.7-1.9 times the mass of the pre-modified alumina nanowires of ethylenediamine were added, and the mixture was stirred for 2-3 hours before filtering, washing with anhydrous ethanol for 3-5 times, and drying at 65-75°C for 8-10 hours to obtain modified alumina nanowires. (2) The modified alumina nanowires, 4-(2-allyl)-catechol, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:(2-3):(0.01-0.02):(4-7), stirred in a nitrogen atmosphere at 80-90°C and 270-290 r / min for 9-11 h, naturally cooled to room temperature and filtered, washed with ethyl acetate for 3-5 times, and dried at 95-105°C for 8-10 h to obtain functionalized alumina nanowires; (3) Mix phenolic epoxy resin, 4-aminophenylboronic acid pinacol ester, 3-aminopropyltrimethoxysilane and deionized water in a mass ratio of 1:(0.6-0.7):(0.3-0.4):(6-8), add 0.9-1.1 mol / L sodium hydroxide solution to adjust the solution pH to 9-11, stir at 40-50°C and 400-500 rpm for 9-11 hours, cool naturally to room temperature, wash with deionized water for 3-5 times, and distill under reduced pressure at 115-125°C for 1-2 hours to obtain a modified phenolic epoxy resin; (4) mixing the modified phenolic epoxy resin and N,N-dimethylformamide in a mass ratio of 1:(0.8-0.9) to obtain a modified phenolic epoxy resin solution; Functionalized alumina nanowires and ethanol solution with a mass fraction of 80-90% are mixed in a mass ratio of 1:(3-4), stirred at 20-30°C and 270-290r / min for 30-40min, and a modified phenolic epoxy resin solution with a mass of 61-62 times that of the functionalized alumina nanowires is added, and ultrasonic dispersion is performed for 25-35min to obtain a heat-resistant and creep-resistant adhesive.
2. The method for preparing a heat-resistant and creep-resistant adhesive according to claim 1, characterized in that: The reaction equation of the pre-modified alumina nanowires in step (1) is: 。 3. The method for preparing a heat-resistant and creep-resistant adhesive according to claim 1, characterized in that: The reaction equation for modifying the alumina nanowires in step (1) is: 。 4. The method for preparing a heat-resistant and creep-resistant adhesive according to claim 1, characterized in that: The reaction equation for functionalizing the aluminum oxide nanowires in step (2) is: 。 5. The method for preparing a heat-resistant and anti-creep adhesive according to claim 1, characterized in that: The reaction equation of the modified phenolic epoxy resin in step (3) is: 。
Citation Information
Patent Citations
Creep-resistant insulating engineering plastic and preparation method thereof
CN115584102A
Green environment-friendly water-based adhesive and preparation method thereof
CN115678468A